The Role of Green Gastronomy-Based Gastronomy as a Sustainable Culinary Tourism Attraction: A Case Study in Surya Kencana, Bogor - Agustiani, Fitri; Malik, Irvan; Zuhdi Naufal, Difa; Lumongga Marpaung, Elizabeth; Wulan, Saptarining (Politeknik Siber Cerdika Internasional, 2025)
The Surya Kencana area in Bogor City is a culinary and cultural center that is full of historical values and ethnic diversity, especially Chinese, Sundanese, and Betawi. However, the region faces challenges due to climate change, urbanization, and environmental degradation that threaten the preservation of local cultures and food systems. This research aims to identify regional revitalization strategies through the green gastronomy approach, namely culinary practices that are sustainable, environmentally friendly, and based on local wisdom. Using qualitative methods with field observations, interviews, and document studies, this study found that the preservation of heritage buildings, the use of local and seasonal foodstuffs, waste management, and community education are important pillars in the transformation of Surya Kencana as a sustainable gastronomic tourism destination. The study also highlights the potential of rare fruits such as menteng and alkesa as innovative elements in local culinary development. A comparison with green gastronomy practices in Bali shows that Surya Kencana has a great opportunity to become the